Corporate tax and foreign direct investment in developing countries - Ong, Tze San; Wong, Koh Cheng; Teh, Boon Heng (TechScience Publications, 2012)
Using data on US multinational enterprises (MNEs) outward foreign direct investment (FDI) between 2000 and 2009, this paper aims to investigate the relationship between corporate tax rate and FDI in developing countries, and contrast the differences in regional corporate tax rates in order to reveal an asymmetry between developed and developing countries. This paper identifies the nature and the relationship between the four independent variables (GDP, trade openness, statutory corporate tax and distance) and U.S. outwards FDI in developing countries. The results indicate that (i) FDI is strongly and positively correlated to market size as well as to trade openness in both types of host countries - developing and developed countries. Also, FDI is inversely correlated to the distance between home and host developed countries, but no significant relationship between home and host developing countries. (ii) US MNEs are negatively influenced by the level of statutory corporate tax rates in host developing countries.